Long-Term Disease Control After locoregional Pelvic Chemoradiation in Patients with Advanced Anal Squamous Cell Carcinoma - Grave, Athénaïs; Blanc, Julie; De Bari, Berardino; Pernot, Mandy; Boulbair, Fatiha; Noirclerc, Monique; Vienot, Angélique; Kim, Stefano; Borg, Christophe; Boustani, Jihane (Frontiers in Oncology, 2022)
Introduction: The incidence of metastatic squamous cell carcinoma of the anus (SCCA) is increasing. Even if systemic docetaxel, cisplatin and 5-Fluorouracil (DCF) provides a high rate of long-term remission, the role of pelvic chemoradiation (CRT) is unknown in this setting. We reported the safety and efficacy of local CRT in patients with synchronous metastatic SCCA who achieved objective response after upfront DCF. Methods: Patients included in Epitopes HPV01 or 02 trials and treated with DCF followed by pelvic CRT were included. Concurrent chemotherapy was based on mitomycin (MMC) (10 mg/m² for two cycles) and fluoropyrimidine (capecitabine 825 mg/m² twice a day at each RT treatment day or two cycles of intra-venous 5FU 1000 mg/m² from day 1 to day 4). Primary endpoints were safety, local complete response rate, and local progression-free survival (PFS). Secondary endpoints were PFS, overall survival (OS), and metastasis-free survival (MFS). Results: From 2013 to 2018, 16 patients received DCF followed by a complementary pelvic CRT for advanced SCCA. Median follow-up was 42 months [range, 11-71]. All patients received the complete radiation dose. Compliance to concurrent CT was poor. Overall, 13/15 of the patients (87%) had at least one grade 1-2 acute toxicity, and 11/15 of the patients (73%) had at least one grade 3-4 toxicity. There was no treatment-related death. The most frequent grade 3-4 adverse effects were neutropenia (36%), dermatitis (40%), and anitis (47%). Eleven patients (73%) had at least one chronic grade 1 or 2 toxicity. One patient had a grade 4 chronic rectitis (7%). Complete local response rate was 81% at first evaluation and 62.5% at the end of the follow-up. Median local PFS was not reached, and the 3-year local PFS was 77 % (95%CI 76.8-77). Conclusions: In patients with metastatic SCCA who had a significant objective response after upfront DCF, local CRT was feasible with high complete local response rate. The good local control rate despite interruptions due to toxicities and low CT compliance, underline the role of pelvic RT. The high rate of toxicity prompts the need to adapt CRT regimen in the metastatic setting.